EVALUATION FOR NEPHROPROTECTIVE ACTIVITY OF ETHANOLIC EXTRACT OF ALLIUM CEPA LINN. IN GENTAMICIN-INDUCED NEPHROTOXICITY IN RATS - Chinnala, Krishna Mohan; Achanta, Prathyusha; Vangala, Vijaya Laxmi; Elsani, Madhan Mohan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Kidney diseases are a major problem of worldwide proportions, and renal damage is very common since kidney has the capacity to excrete toxic substances. This study aimed to evaluate the protective effect of the ethanolic extract of Allium cepa Linn. (EEAC) plant leaves against gentamicininduced nephrotoxicity in rats. Methods: Nephroprotective activity was estimated by inducing gentamicin (100 mg/kg) to all the groups of animals; acute kidney dysfunction is an evidenced by significant elevation of serum creatinine, total protein and decreased body weight with multiple histological damages. Results: Treatment with the A. cepa Linn. has shown significant (p<0.01 and p<0.001) dose-dependent improvement in the body weight at the dose of 200 and 400 mg/kg and also shown significant improvement by protecting the kidney from the oxidative stress. It is also identified that treatment with A. cepa significantly lowered the level of serum creatinine, total protein when compared with the toxic group. Conclusion: Nephroprotective activity of EEAC treatment was found compared with the standard group (Vitamin E – 250 mg/kg) and control group against the toxic control group animals in parameters including serum creatinine, total protein, kidney weights, and body weights. The histopathological studies were also evinced the protective effect of EEAC. Keywords: Nephroprotective activity, Gentamicin, Nephrotoxicity, Allium cepa Linn.